Scandinavian baking loving baking at home - Hahnemann, Trina (Quadrille Publishing, 2014)
A world of steamed-up kitchen windows against a frosty backdrop, delicious Danish pastries, crusty dense breads and creamy layer cakes is summoned up in Trine Hahnemann's spectacularly beautiful new book, Scandinavian Baking. Cakes abound, with every kind of Danish pastry you could ever wish for, a cookie for every occasion, mouthwatering layer cakes, coffee cakes, cream buns plus snippets of baking history, so you can learn all you need to know about Scandinavian baking. Divided into two main sections on cakes and breads, sandwiched between features on Midsummer and Christmas, this is the ultimate compendium on authentic Scandinavian baking with a modern twist